Familias disfuncionales y su relación con el aprendizaje en niños de cuatro y cinco años de la I.E.I.P.S.M Nº 601606 Violeta Correa de Belaunde en el distrito de Belén, Loreto, 2022 - Del Castillo Catanga, Alicia Yamile (2024)
A research study was conducted with the aim of determining the relationship between dysfunctional families and learning in four- and five-year-old children at the I.E.I.P.S.M Nº 601606 Violeta Correa de Belaunde in Belén, 2022. A quantitative non-experimental research approach and a descriptive-correlational design were considered for this purpose. The Family APGAR questionnaire and observation sheets assessing cognitive learning were used as measurement instruments. These instruments were validated by experts in the field. The study population included all students from the mentioned educational institution, with a sample size of 110 children from the 4- and 5-year-old classrooms. The research findings concluded that there is an inverse relationship between dysfunctionality and learning. The Pearson correlation coefficient resulted in rxy = - 0.719, indicating a strong, inverse, and negative relationship between both variables. As dysfunctionality decreases, students may experience an improvement in learning.